Respons Pertumbuhan Berbagai Ukuran Diameter Batang Stek Bugenvil (Bougainvillea spectabilisWilld.) Terhadap Pemberian Zat Pengatur Tumbuh - Leo Richi H Panjaitan; Jasmani Ginting; Haryati Haryati (Jurnal Agroekoteknologi, 2014)
Successive percentage of bugenvil plant propagation by cutting method is low enough sincebugenvil is difficult to rooting plant. The availability of carbohydrate source and plant growthregulator in the stem cutting are factors that influencing the successive of cutting. Solution to solvethis problem is selection of the size of stem and giving the exsogen plant growth regulator. Theresearch was done in Screen House at Agricultural Faculty, University of North Sumatra, Medan inJanuary until August 2013 to study the growth of sizes of diameter stem cutting with application ofthe growth regulators. The design of the research used randomized block design of factorial withtwo factors of treatment and three replications. The first factor was diameters of stem cutting which6, 12 and 18 mm. The second factor was application of the plant growth regulator IBA + BAPwhich control, 400+ 400 ppm, 600 + 600 ppm and 800 + 800 ppm. Parameters were shoot height,shoot diameter, root fresh weight of sample, root dry weight of sample, shoot fresh weight ofsample, and shoot dry weight of sample. The results showed that diameter 18 mm and giving ofplant growth regulator 800 + 800 ppm gave the great influence in cutting growth.Key words : size of diameter stem cutting, plant growth regulator, bugenvil